Does inguinal hernia repair increase urinary retention? Our 10-year results - Efendiye, Ferec; Celasin, Haydar (International Surgery Journal, 2021)
Background: This study aimed to determine the incidence of urinary retention in patients undergoing inguinal hernia repair at our hospital as well as the predictors of urinary retention. Methods: Patients who underwent inguinal hernia repair at Lokman Hekim university Akay hospital between January 2010 and January 2020 were included in the study. The total number of patients was 578. The patients were divided into two groups: group-1 (patients who developed urinary retention following inguinal hernia repair) and group-2 (patients who did not develop urinary retention following inguinal hernia repair). The relationship between urinary retention and age, history of preoperative BPH, type and localization of hernia, operative and anesthesia time, perioperative NSAID, narcotic analgesic and antispasmodic use, presence of DM and rheumatic diseases and perioperative fluid replacement was investigated. Results: The median ages were 57.7±15.1 (20-74) and 48.8±17.5 (18-89) in groups 1 and 2, respectively (p<0.001). 5.36% (31/578) of the patients developed urinary retention. The group-1 were found to be at a more advanced age (p<0.001), have higher rates of BPH and DM (p<0.001), longer operative time (p<0.001), higher rate of perioperative antispasmodic use (p<0.001), higher rate of perioperative fluid replacement (p<0.001) and a lower rate of perioperative NSAID use (p<0.001) compared to those who did not develop postoperative urinary retention. Conclusions: According to the results of this study, advanced age, history of DM and BPH, antispasmodic use, longer operative time, high amount of postoperative fluid replacement and no perioperative use of NSAIDs lead to an increased risk of urinary retention.